Calcium Sulfate Dihydrate (gypsum) Quality Test Using Radiography Non Destructive Test (RNDT) - Himawan, Hendra; Tauﬁq, Ulil Albab; Setiawan, Rudi; ., Masturi; ., Susilo; Dwijananti, Pratiwi (KnE Social Sciences, 2019)
Calcium Sulfate Dyhidrate/gypsum is a material commonly found in nature which is used at industrial site for making a wall, roof, etc. One of the problems found in material industry is crack deffect, white crack defects is very difﬁcult be identiﬁed it visibility. Radiography Non-Destructive Test (RNDT) is non destructive test supported by digital radiographic producing digital image. This work aims to determine the gypsum properties to ﬁnd out crack defect using RNDT. Radiographic image depends on exposure factors (kV, mA, s, and SID). Digital image can be proceed using OctaveGUI to determine the crack defect area, image processing using Prewitt detection. Radiographic digital result of 3gypsumboards (a,bandc) and 2gypsumpro ﬁlsamples (d and e) were found the crack on each samples. RNDT was perfomed using X-ray voltageat60kVona,b,c,d,andesamples.Eachsamplescrackareavalueare158.13 mm2; 127.43 mm2; 196.81 mm2; 73.97 mm2; dan 18.80 mm2. Others RNDT was using X-ray voltage at 70 kV on samples a, b, c, d, and e. Each samples crack area value are 220.62 mm2; 1,711.57 mm2; 209.33 mm2; 76.50 mm2; dan 11.18 mm2. In conlusion, the crack area values obtained can be used as RNDT. Keywords: X-ray, Gypsum, RNDT, Image Processing.